The Term ʿālam in 1 Enoch - Assefa, Daniel (Aethiopica, 2015)
In 1 Enoch, the term ʿālam offers various meanings, most of which are temporal. It qualifies God as well as heaven. It also expresses the type of angelic life in heaven. With regard to life on earth, ʿālam signifies the most distant past and the most distant future. It also refers to things that will have a long duration, yet not without limit, like the suffering of fallen angels. In contrast human suffering on earth is never associated with an eternal one.